2014
DOI: 10.3790/sfo.63.9.238
|View full text |Cite
|
Sign up to set email alerts
|

Gesundheitsökonomische Evaluation des Disease Management-Programms “Diabetes mellitus Typ 2“ der Knappschaft

Abstract: Health-economic evaluation of the Disease Management-Programme "Diabetes mellitus Type 2" of the Knappschaft Bahn See

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
6
0
1
Order By: Relevance
“…Since then a higher percentage of patients is enrolled in the DMP CAD, which might have changed the patient characteristics in the DMP over time. Whereas so far no economic analyses were conducted on health care expenditures for the DMP CAD in Germany, there are previous studies that focused on the DMPs COPD [35] and type 2 diabetes [13,[36][37][38][39][40]. In COPD, Achelrod et al [35] conducted a study using data of a statutory health insurance fund and found that expenditures for hospitalization, ambulatory care and medication were significantly higher in the DMP group, leading to significantly higher total health care expenditures.…”
Section: Comparison Of Findings With Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…Since then a higher percentage of patients is enrolled in the DMP CAD, which might have changed the patient characteristics in the DMP over time. Whereas so far no economic analyses were conducted on health care expenditures for the DMP CAD in Germany, there are previous studies that focused on the DMPs COPD [35] and type 2 diabetes [13,[36][37][38][39][40]. In COPD, Achelrod et al [35] conducted a study using data of a statutory health insurance fund and found that expenditures for hospitalization, ambulatory care and medication were significantly higher in the DMP group, leading to significantly higher total health care expenditures.…”
Section: Comparison Of Findings With Literaturementioning
confidence: 99%
“…In COPD, Achelrod et al [35] conducted a study using data of a statutory health insurance fund and found that expenditures for hospitalization, ambulatory care and medication were significantly higher in the DMP group, leading to significantly higher total health care expenditures. Concerning type 2 diabetes, to date seven publications based on statutory health insurance claims data reported cost measures for the DMP type 2 diabetes [13,[36][37][38][39][40]. Five studies [13,36,38,39] reported overall health care expenditures-all of these studies reported lower costs in the DMP group, but only in two studies [36,38] the results were significant.…”
Section: Comparison Of Findings With Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Alternati ven sind eine Adjustierung über Regres sionsmethoden oder andere kausalitäts erklärende Verfahren wie FixedEffects Modelle, Instrumentenvariablen oder die RegressionsDiskontinuitätsAnaly se [34] bis hin zu wissensbasierten Ver fahren wie den vielversprechenden kau salen Graphen (Directed Acyclic Graphs [35]). Auch ein DifferenzinDifferenzen Ansatz ist alternativ oder additiv möglich [36]. Hinsichtlich der Wahl des zu mes senden Outcomes ist -nach gewissen Er nüchterungen bei der Messung der Ergeb nisqualität mit Surrogatparametern [37] ein Trend zu beobachten hin zur Prozes squalität [38], die sich dank einer nahe zu kompletten (weil abrechnungsrelevan ten) Leistungshistorie in den Routineda ten hervorragend abbildet.…”
Section: Vergleichende Studienbeurteilungunclassified